Prognostic analysis according to the 2017 ELN risk stratification by genetics in adult acute myeloid leukemia patients treated in the Japan Adult Leukemia Study Group (JALSG) AML201 study. (March 2018) - Harada, Yasuhiko; Nagata, Yasunobu; Kihara, Rika; Ishikawa, Yuichi; Asou, Norio; Ohtake, Shigeki; Miyawaki, Shuichi; Sakura, Toru; Ozawa, Yukiyasu; Usui, Noriko; Kanamori, Heiwa; Ito, Yoshikazu; et al.
Highlights: The ELN-2017 risk system distinguished the prognosis of Japanese AML patients. The FLT3 -ITD low was not necessarily associated with a better prognosis. Cytogenetics may affect the prognosis in patients with favorable genetic lesions. Abstract: Many genetic alterations that are associated with the prognosis of acute myeloid leukemia (AML) have been identified, and several risk stratification systems based on the genetic status have been recommended. The European LeukemiaNet (ELN) first proposed the risk stratification system for AML in 2010 (ELN-2010), and recently published the revised system (ELN-2017). We validated the long-term prognosis and clinical characteristics of each ELN-2017 risk category in Japanese adult AML patients who were treated in the Japan Adult Leukemia Study Group (JALSG) AML-201 study. We demonstrated that the 3-risk category system of the ELN-2017 successfully discriminated the overall survival and complete remission rates in our cohort in comparison with the 4-risk category of the ELN-2010. However, there were still genetic categories in which stratification of patients into favorable or intermediate risk categories was controversial; the low allelic ratio of FLT3 -ITD was not necessarily associated with a better prognosis in patients with FLT3 -ITD, and cytogenetic abnormalities may affect the prognosis in patients with favorable genetic lesions such as NPM1 and CEBPA mutations. As many molecular targeting agents, such as FLT3 inhibitors, have been developed, we must continue to modify the genetic risk stratification system to match the progression of therapeutic strategies.